Efficacy and Safety of AmBisome in Combination with Sodium Stibogluconate or Miltefosine and Miltefosine Monotherapy for African Visceral Leishmaniasis: Phase II Randomized Trial. - Monique Wasunna; Simon Njenga; Manica Balasegaram; Neal Alexander; Raymond Omollo; Tansy Edwards; Thomas P C Dorlo; Brima Musa; Mohammed Hassan Sharaf Ali; Mohammed Yasein Elamin; George Kirigi; Rashid Juma; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:SSG&PM over 17 days is recommended as first line treatment for visceral leishmaniasis in eastern Africa, but is painful and requires hospitalization. Combination regimens including AmBisome and miltefosine are safe and effective in India, but there are no published data from trials of combination therapies including these drugs from Africa. METHODS:A phase II open-label, non-comparative randomized trial was conducted in Sudan and Kenya to evaluate the efficacy and safety of three treatment regimens: 10 mg/kg single dose AmBisome plus 10 days of SSG (20 mg/kg/day), 10 mg/kg single dose AmBisome plus 10 days of miltefosine (2.5mg/kg/day) and miltefosine alone (2.5 mg/kg/day for 28 days). The primary endpoint was initial parasitological cure at Day 28, and secondary endpoints included definitive cure at Day 210, and pharmacokinetic (miltefosine) and pharmacodynamic assessments. RESULTS:In sequential analyses with 49-51 patients per arm, initial cure was 85% (95% CI: 73-92) in all arms. At D210, definitive cure was 87% (95% CI: 77-97) for AmBisome + SSG, 77% (95% CI 64-90) for AmBisome + miltefosine and 72% (95% CI 60-85) for miltefosine alone, with lower efficacy in younger patients, who weigh less. Miltefosine pharmacokinetic data indicated under-exposure in children compared to adults. CONCLUSION:No major safety concerns were identified, but point estimates of definitive cure were less than 90% for each regimen so none will be evaluated in Phase III trials in their current form. Allometric dosing of miltefosine in children needs to be evaluated. TRIAL REGISTRATION:The study was registered with ClinicalTrials.gov, number NCT01067443.